In vitro effect of low-fluoride toothpaste supplemented with sodium trimetaphosphate, xylitol, and erythritol on enamel demineralization - Oliveira, Letícia Gonçalves [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Gonçalves, Francyenne Maira Castro [UNESP]; Fernandes, Gabriela Leal Peres [UNESP]; Cannon, Mark L.; Danelon, Marcelle [UNESP] (FapUNIFESP (SciELO), 2023)
Regular use of toothpaste with fluoride (F) concentrations of ≥ 1000 ppm has been shown to contribute to reducing caries increment. However, when used by children during the period of dental development, it can lead to dental fluorosis. Objective: In this study, we aimed to evaluate the in vitro effect of a toothpaste formulation with reduced fluoride (F) concentration (200 ppm) supplemented with sodium trimetaphosphate (TMP: 0.2%), Xylitol (X:16%), and Erythritol (E: 4%) on dental enamel demineralization. Methodology: Bovine enamel blocks were selected according to initial surface hardness (SHi) and then divided into seven experimental toothpaste groups (n=12). These groups included 1) no F-TMP-X-E (Placebo); 2) 16% Xylitol and 4% Erythritol (X-E); 3) 16% Xylitol, 4% Erythritol and 0.2%TMP (X-E-TMP); 4) 200 ppm F (no X-E-TMP: (200F)); 5) 200 ppm F and 0.2% TMP (200F-TMP); 6) 200 ppm F, 16% Xylitol, 4% Erythritol, and 0.2% TMP (200F-X-E-TMP); and 7) 1,100 ppm F (1100F). Blocks were individually treated 2×/day with slurries of toothpastes and subjected to a pH cycling regimen for five days (DES: 6 hours and RE: 18 hours). Then, the percentage of surface hardness loss (%SH), integrated loss of subsurface hardness (ΔKHN), fluoride (F), calcium (Ca), and phosphorus (P) in enamel were determined. The data were analyzed by ANOVA (1-criterion) and the Student-Newman-Keuls test (p<0.001). Results: We found that the 200F-X-E-TMP treatment reduced %SH by 43% compared to the 1100F treatments (p<0.001). The ΔKHN was ~ 65% higher with 200F-X-E-TMP compared to 1100F (p<0.001). The highest concentration of F in enamel was observed on the 1100F treatment (p<0.001). The 200F-X-E-TMP treatment promote higher increase of Ca and P concentration in the enamel (p<0.001). Conclusion: The association of 200F-X-E-TMP led to a significant increase of the protective effect on enamel demineralization compared to the 1100F toothpaste.
Keywords: Dental enamel; Erythritol; Fluoride; Phosphate; Tooth demineralization; Xylitol